Short communication. Effect of deficit irrigation on curly lettuce grown under semiarid conditions - Kuslu, Y.=700 1 Dursum, A.; Sahin, U.; Kiziloglu, F.M.; Turan, M.
(En, Es)
Ilus., 22 ref.
Keywords: LACTUCA SATIVA; RENDIMIENTO; EVAPOTRANSPIRACION; OLIGOELEMENTOS; ESPAÑA; LECHUGA RIZADA; MACROELEMENTOS; SPANISH JOURNAL OF AGRICULTURAL RESEARCH